BEHAVIOR ASSESSMENT SYSTEM FOR LINEAR DISCRETE-DIMENSIONAL INVARIANT UP TO THE TIME - SYLVIANI (NIM : 20110301), SISILIA
This thesis shows that for a time invariant finite dimensional discrete linear system, the concept of behavior which was introduced by Fuhrmann in 2002 can be seen as an extension of the behavior concept which was introduced by Willems in 1986. Willems introduces a dynamic system as a triple. This deffinition of the dynamical system is very general and can be described independently. The behavior of a dynamical system, in Willemss point of view is the set of all trajectories of the system. Meanwhile, Fuhrmann adopted Willemss concept of behavior for discrete linear system, On the other hand, Fuhrmann does not state the behavior of a time invariant discrete linear system as the set of all trajectories of the system. Fuhrmann defines the behavior as a linear, shift invariant, and complete subspace.